A study of service quality in Indian public sector banks using modified SERVQUAL model - Dasharathraj K Shetty; Nikhil Perule; Srinivasa Rao Potti; Maulik Jain; Namesh Malarout; Sonal Devesh; Sonia F Vaz; Babita Singla; Nithesh Naik (Cogent Business & Management, 2022)
Assessment of service quality has been widely utilized in the service sector, especially in the banking industry. The present study aims to understand the influence of service quality on customer loyalty in Indian public sector banks. The service quality is quantified with the help of a modified SERVQUAL model using dimensions Reliability, Assurance, Tangibles, Empathy, Responsiveness, Charges, and Convenience. Structural equation modelling (SEM) indicated that among all the dimensions, Assurance, Empathy, Responsiveness, and Tangible were found to have a significant relationship with service quality. The banks must focus on bringing in innovation in these parameters to maintain a high quality of service and achieve higher satisfaction, which subsequently develops customer trust towards the company. By bringing innovative changes to improve the service quality, the banks can also increase their competitive advantage and customer retention as service quality has a significant relationship with customer loyalty.
Keywords: 650; Banking; public sector banks; service quality; SERVQUAL; structural equation modelling